Small‐angle neutron scattering by spatially inhomogeneous ferromagnets with a nonzero average uniaxial anisotropy. Issue 3 (1st June 2022) - Zaporozhets, V. D.; Oba, Y.; Michels, A.; Metlov, K. L.
Abstract : Macroscopic spin‐misalignment small‐angle neutron scattering cross sections and response functions are computed analytically for a material with global uniaxial magnetic anisotropy (texture). The resulting expressions are tested against previously published experimental data. Abstract : Micromagnetic small‐angle neutron scattering theory is well established for analyzing spin‐misalignment scattering data of bulk ferromagnets. Here, this theory is extended to allow for a global uniaxial magnetic anisotropy (texture) of the material, in addition to the already included random zero‐average local anisotropy. Macroscopic cross sections and spin‐misalignment response functions are computed analytically for several practically relevant mutual anisotropy and external magnetic field orientations in both parallel and perpendicular scattering geometries for field magnitudes both above and below the rotational saturation. Some of these expressions are tested on published experimental data of magnetic‐field‐annealed Vitroperm and plastically deformed Ni, allowing determination of the corresponding global uniaxial anisotropy quality factors.